Catalase, protease and urease activity in some types of soil - Purev, D; Bayarmaa, J; Ganchimeg, B; Ankhtsetseg, B; Anumandal, O (Mongolian Journal of Chemistry, 2014)
DOI: http://dx.doi.org/10.5564/mjc.v13i0.153 Mongolian Journal of Chemistry Vol.13 2012: 16-18